Unusual Complications of Anterior Cervical Discectomy and Fusion: Report of Two Cases - Shrestha, Prabin; Yamaguchi, Satoshi (Nepal Journal of Neuroscience, 2026)
Background: Anterior cervical discectomy and fusion (ACDF) is the most common surgical procedure of cervical spine, and its number has drastically increased in recent years due to advancement in technology and technique. Most of the time, it is safe and effective. However, unusual complications sometimes can cause devastating outcomes. The main aim of this report is to make surgeons aware of such complications and to prevent unexpected outcomes. Here we present two cases of unusual complications of ACDF.Case Reports: The first case was a 60-year-old female who was planned for ACDF at the level of C3-4-5-6. While dissecting the soft tissues and longus colli (LC) muscle on the right side of the anterior surface of the vertebral body, the vertebral artery (VA) was injured. Immediate endovascular intervention saved the patient's life.The second case was a 50-year-old female with morbid obesity and was planned for ACDF at C6-7. Because of a short and thick neck, retraction was difficult. Postoperatively she developed visual symptoms due to right Horner’s syndrome.Conclusion: Complications happen after surgery. However, every effort should be made to prevent them, especially those which can endanger the patient’s life. Careful preoperative evaluation of patient and radio-imaging often gives hints most of the time.